Annular Systolic Velocity Predicts the Presence of Spontaneous Echo Contrast in Mitral Stenosis Patients with Sinus Rhythm - Çayli, Murat (Clin Cardiol, 2007)
OJECTIVES: Thromboembolism is the major cause of morbidity and mortality in mitral stenosis (MS), even in sinus rhythm (SR). Spontaneous echo contrast (SEC) is the strongest predictor of thromboembolism. The aim of the study was to investigate if the annular velocities obtained with tissue Doppler imaging can predict the presence of SEC in MS patients with SR. METHODS: One hundred and five MS patients and 100 controls were included. Annular velocities were recorded. All patients underwent transesophageal echocardiography. Subjects were divided into three groups as controls (Group I), the patients without SEC (Group II) and the patients with SEC (Group III). RESULTS: Group III patients had lower ejection fraction, annular systolic velocity, smaller mitral valve area, higher transmitral gradient and larger left atrial size. The annular systolic velocity was the only independent predictor for SEC. The cutoff values of annular systolic velocity for prediction of the presence of any SEC and dense SEC were 13.5 and 11.8 cm/s, respectively. CONCLUSION: The annular systolic velocity is an independent predictor for SEC in MS patients with SR. Copyright © 2007 Wiley Periodicals, Inc.